2010
DOI: 10.1057/bm.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Brand strategies of Jordanian telecommunications service providers

Abstract: This article reports on an exploratory investigation into the brand strategy of the telecommunications service providers in Jordan, and thereby contributes to the limited research into brand strategy in both the telecommunications sector, and in the Middle-Eastern countries. The study demonstrates the extent to which the evolution of competitive strategy and brand strategy are interwoven, as well as generates a range of insights into successful brand strategies in this marketplace. It specifi cally responds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(57 reference statements)
1
8
0
1
Order By: Relevance
“…(2016) , for example, found that prices significantly and positively influenced consumers’ brand preference. Such finding is consistent with the previous findings of the research done by Alamro and Rowley (2011) . Therefore, it can be asserted that consumers are willing to pay a higher price for a brand that have high value, and vice versa ( Erdem et al., 2004 ).…”
Section: Theoretical Background and Hypothesissupporting
confidence: 94%
See 1 more Smart Citation
“…(2016) , for example, found that prices significantly and positively influenced consumers’ brand preference. Such finding is consistent with the previous findings of the research done by Alamro and Rowley (2011) . Therefore, it can be asserted that consumers are willing to pay a higher price for a brand that have high value, and vice versa ( Erdem et al., 2004 ).…”
Section: Theoretical Background and Hypothesissupporting
confidence: 94%
“…Price perception also have an impact on consumers' brand preference. Several previous studies have also proven the role of price as an independent factor in consumers' brand preference (e.g., Alamro and Rowley, 2011 ; Hwang and Chung, 2019 ; Petruzzellis and Romanazzi, 2010 ). Ebrahim et al.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 88%
“…Country of origin was included in this study because country of origin (i.e. Jordanian v international) was at the heart of the brand strategies of the competitors in the mobile telecommunications service providers in Jordan (Alamro and Rowley, 2011). It may be less appropriate in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported in this article, then, investigates brand preference in the context of the mobile telecommunications service sector in Jordan. This is part of a wider study of brand strategy in the sector (Alamro and Rowley, 2011). This article makes a contribution to theory by developing a holistic model of the antecedents of brand preference, and also offers insights into the relative impact of the different factors on brand preference.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of services studies concentrate on branding in the telecom industry (Melewar et al 2005;Alamro and Rowley, 2011;Hijab et al 2011;Nguyen et al, 2011). De Chernatony andSegal-Horn (2001) suggest that this lack of attention and consequent lack of services' branding knowledge has led to a paucity of successful services' brands.…”
Section: Background and Research Scopementioning
confidence: 99%